2016
DOI: 10.1097/md.0000000000002564
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil Cytoplasmic Antibodies Associated With Infective Endocarditis

Abstract: To determine the prevalence of antineutrophil cytoplasmic antibodies (ANCA) in patients with infective endocarditis (IE) in internal medicine; and to compare clinical and biochemical features and outcome between patients exhibiting IE with and without ANCA.Fifty consecutive patients with IE underwent ANCA testing. The medical records of these patients were reviewed.Of the 50 patients with IE, 12 exhibited ANCA (24%). ANCA-positive patients with IE exhibited: longer duration between the onset of first symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 77 publications
1
55
1
5
Order By: Relevance
“…Presence of ANCA has been previously reported in 18%-33% of patients with infective endocarditis (21)(22)(23)(24)(25)(26). A recent prospective study by Langlois et al (27) on 50 consecutive patients with infective endocarditis found 12 (24%) to be ANCA positive. Thus, ANCA vasculitis also enters the differential diagnosis, especially for staphylococcal endocarditis.…”
Section: Introductionmentioning
confidence: 92%
“…Presence of ANCA has been previously reported in 18%-33% of patients with infective endocarditis (21)(22)(23)(24)(25)(26). A recent prospective study by Langlois et al (27) on 50 consecutive patients with infective endocarditis found 12 (24%) to be ANCA positive. Thus, ANCA vasculitis also enters the differential diagnosis, especially for staphylococcal endocarditis.…”
Section: Introductionmentioning
confidence: 92%
“…It is noted that all microwave treatments increased the ascorbic acid content available in the juice compared to the nontreated juice. Compared to conventional methods, microwave processing provides heat transfer in food, and the nutrients, vitamins, taste and sensory characteristics, and color of food are well preserved (Ahmed & Ramaswamy, 2007). Furthermore, the conventional technical treatment reduced significantly (p < 0.05) in relation to the control juice.…”
Section: Ascorbic Acidmentioning
confidence: 98%
“…Evidence suggests that infections have a central role in the formation of ANCAs and that chronic infections mimic AAV 99 ; infective endocarditis can mimic ANCA-associated glomerulonephritis and patients with infective endocarditis can develop ANCAs. Langlois et al 100 reported ANCAs by IIF in 12 out of 50 patients (24%) with infective endocarditis; four patients had PR3-ANCAs, one patient had MPO-ANCAs and two patients had both PR3-ANCAs and MPO-ANCAs. Mahr et al 101 reported ANCA by IIF in 20 out of 109 patients (18%) with infective endocarditis (14 patients were positive for C-ANCA and six were positive for P-ANCA); of these, three patients had C-ANCA and PR3-ANCAs, two patients had C-ANCA and MPOANCAs, one patient had P-ANCA and MPO-ANCAs, one patient had just PR3-ANCAs and one patient had just MPO-ANCAs.…”
Section: Recommandationmentioning
confidence: 99%